Formation and characterization of zein-caseinate-pectin complex nanoparticles for encapsulation of eugenol. (March 2018) - Veneranda, Marco; Hu, Qiaobin; Wang, Taoran; Luo, Yangchao; Castro, Kepa; Madariaga, Juan Manuel
Abstract: Three food polymers, zein, sodium caseinate (NaCas) and pectin were exploited as the matrix to formulate colloidal complex nanoparticles for encapsulation of eugenol. A heat- and pH-induced complexation process was optimized via polymer concentrations, loading percentage of eugenol, as well as pH conditions, to obtain small, homogeneous, and stable complex nanoparticles. The particulate properties were significantly affected by pH condition during heating process, and the smallest and most homogeneous complex nanoparticles were obtained when heated at pH 6.6, the isoelectric point of zein. NaCas played an important role to achieve desirable stability during storage and spray drying. Fourier transform infrared spectroscopy indicated that hydrophobic and electrostatic interactions were driving forces to form complex structure. The innovative nano spray drying was tested to transform colloidal nanoparticles to fine powder particles, enabling the long-term storage in powder form and thus a greater potential to the applications in food industry. Under optimal preparation condition and formulation, eugenol-loaded complex nanoparticles with a size of 140 nm, spherical shape and uniform size distribution were obtained and their structure was verified by both scanning and transmission electron microscopies. Highlights: Heating at isoelectric point of zein promoted the formation of smallest particles. Loading eugenol did not alter the structure of complex nanoparticles. Caseinate stabilized complex nanoparticles during spray drying and storage. Dry powders in range of 1–1.5 μm were obtained by innovative nano spray drying. Powders exhibited exceptional redispersibility maintaining original nanoscale size.